2020
DOI: 10.3389/fpls.2020.00441
|View full text |Cite
|
Sign up to set email alerts
|

Multielemental Stoichiometry in Plant Organs: A Case Study With the Alpine Herb Gentiana rigescens Across Southwest China

Abstract: Multiple elements are required to be allocated to different organs to meet the demands for plant growth, reproduction, and maintenance. However, our knowledge remains limited on the stoichiometry in all plant organs in response to heterogeneous environments. Here, we present the systematic investigation of multielemental stoichiometry in organs of the alpine plant Gentiana rigescens across different environmental conditions. The slopes of N-P stoichiometric relationships among organs in G. rigescens did not di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…Our findings concur with those from earlier studies [ 18 , 19 , 20 ]. It is well-known that the composition and content of chemical components of Chinese herbs change with soil conditions, cultivation measures and climate factors in the growth process [ 21 , 22 , 23 , 24 , 25 ]. In addition, relevant studies have shown that the primary processing, storage time and storage method of TCMs also affect the quality of Chinese herbs [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings concur with those from earlier studies [ 18 , 19 , 20 ]. It is well-known that the composition and content of chemical components of Chinese herbs change with soil conditions, cultivation measures and climate factors in the growth process [ 21 , 22 , 23 , 24 , 25 ]. In addition, relevant studies have shown that the primary processing, storage time and storage method of TCMs also affect the quality of Chinese herbs [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…ex Hemsl. that concentration of K is higher in flowers than in other plant tissues [ (Zhang et al, 2020); unfortunately Na was not considered in that study]. Future studies might elucidate the role of K:Na nutritional limitation in the ecology and evolution of bees.…”
Section: Discussionmentioning
confidence: 97%
“…Age-related nutrient storage strategies for active organs in forests of different origins Age-related changes in plantations and natural forests were distinctly summarized. Practically all active organs exhibited a certain reduction in their P concentrations (Fownes, 1995 In forest ecosystems, leaves, litter, and ne roots have rapid turnover rates, which are also functional drivers of nutrient cycling (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%